2019
DOI: 10.1002/ijc.32739
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic variants in KIF16B and NEDD4L in the endosome‐related genes are associated with nonsmall cell lung cancer survival

Abstract: The endosome is a membrane-bound organ inside most eukaryotic cells, playing an important role in adaptive immunity by delivering endocytosed antigens to both MHC class I and II pathways. Here, by analyzing genotyping data from two published genome-wide association studies (GWASs), we evaluated associations between genetic variants in the endosome-related geneset and survival of patients with nonsmall cell lung cancer (NSCLC). The discovery included 44,112 (3,478 genotyped and 40,634 imputed) single-nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
4
10
0
Order By: Relevance
“…However, the detailed role of NEDD4-like proteins in LUAD pathogenesis is still unclear. Here, our integrated bioinformatics analysis demonstrated a prognostic value of NEDD4L in LUAD, which was consistent with the results observed by Yang et al in lung cancer [33]. GSEA results indicated that genes regulated by NEDD4L were enriched in the mTORC1 pathway (Figure 3A&3B).…”
Section: Discussionsupporting
confidence: 91%
“…However, the detailed role of NEDD4-like proteins in LUAD pathogenesis is still unclear. Here, our integrated bioinformatics analysis demonstrated a prognostic value of NEDD4L in LUAD, which was consistent with the results observed by Yang et al in lung cancer [33]. GSEA results indicated that genes regulated by NEDD4L were enriched in the mTORC1 pathway (Figure 3A&3B).…”
Section: Discussionsupporting
confidence: 91%
“…It suggested that NEDD4L acted as an anti-oncogene in BRCA, consistent with Lee's study [32]. Previous studies have shown that NEDD4L plays an anti-cancer role in carcinomas, such as glioma, lung cancer, and colorectal cancer [23,33,34]. Furthermore, we performed GO and KEGG analysis and found that the differential genes between the two subgroups enriched in the TGF-β pathway, which plays a vital role in the EMT and metastasis of BRCA [4].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, NEDD4L expression was appreciably link to the clinical outcome of CN-AML. Although it is the first report regarding the prognostic significance of NEDD4L expression in AML, several studies have shown the great correlations of NEDD4L expression with clinical outcome in solid tumors [ 9 16 ]. Reduced expression of NEDD4L correlated with adverse prognosis in non-small cell lung cancer, gastric cancer, hepatocellular carcinoma, ovarian cancer, and malignant glioma [ 9 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…NEDD4L is originally discovered in identifying for downregulated genes during the development of the central nervous system [ 7 , 8 ]. Recently, there is mounting evidence that showed the association of NEDD4L expression with prognosis in diverse human cancers [ 9 16 ].…”
Section: Introductionmentioning
confidence: 99%